ANALISIS PENGARUH AKTOR PADA TAGAR #ROKETCHINA DI MEDIA SOSIAL TWITTER MENGGUNAKAN SOCIAL NETWORK ANALYSIS (SNA) - Chryshella Jovanica; Denok Dwi Rahmintaningrum; Hanin Annisa Nuradni; Anisa Salsabila (Jurnal Ilmiah Komunikasi Makna, 2022)
The world was shocked by the news that the Chinese rocket had fallen back to earth. The news attracted the attention of the public from foreign countries to the people of Indonesia. With the presence of news on Chinese rockets, social media, one of which is Twitter, has the trending hashtag #roketchina which is widely discussed by Indonesians. This study aims to determine social networking in conversations on twitter using the hashtag #roketchina. In this study using a social network analysis research method by analyzing participant observation. The results of this study describe the communication network formed based on the hashtag #roketchina. In this network there are 12 actors and 40 ties or accounts interacting on the hashtag #roketchina. In addition, there are two types of relationships on social media twitter using the hashtag #roketchina (two modes), because communication networks are not only monitored by individuals but also official institutions or agencies. In addition, there is a Y-shaped communication network pattern, where the perpetrators have the initiative to give or even receive information about the hashtag #roketchina.